Student’s spending habit in Universiti Teknologi Mara (UiTM), Sarawak/ Micheal Kadong Grunsin, Shasha Belayong& Warick Mandes - Grunsin, Micheal Kadong; Belayong, Shasha; Mandes, Warick
Financial is important for everyone and they need to manage their financial with properly because without a good or proper management of financial, the problem may occurs such as overspending, do not have enough money to buy food, no saving for future use, and so on. Thus, parents should teach their children how to manage their financial with properly and show good example in order to give notable example to their children.As the students of university, they should know how to manage their financial with appropriate. This is because, they already mature and had been provide with enough money by their parent and had full right on their own money and spend their money to do their routine like buy food, buy clothing, and necessaries item.